The effect of supply chain management practices based on enterprise resource planning systems on retail performance through competitive advantage - Dwita, Febrisi; Sumardiono, Sumardiono; Apriani, Rika; Agustine, Leony; Rivaldo, Tri Luis (Universitas Tarumanagara, 2023)
The rapid growth of retailers has resulted in increasingly fierce business competition in the market for the sale of goods and services offered to achieve excellence. One of the best service strategies for introducing various innovations in enterprise resource planning is to capture consumer interest in using these services. This study aims to examine and analyze the relationship between supply chain management practices based on enterprise resource planning (ERP) systems and business performance through competitive advantages of companies. Retail Bekasi area. This study was done. The questionnaire for each variable was distributed as a representative question of all dimensions with a sample of 200 respondents. For data analysis, we use SEM using AMOS software. In the end, the following search results were obtained: SCM practices have a positive and significant impact on competitive advantage, hypothesis 1 is accepted; (2) ERP system has a positive and significant impact on competitive advantage, hypothesis 2 is accepted; (3) SCM practices have a positive and significant impact on company performance, hypothesis 3 is accepted; (4) ERP system has a positive and significant impact on business performance, hypothesis 4 is accepted; (5) Competitive advantage has a positive and significant impact on business performance, hypothesis 5 is accepted. Pesatnya pertumbuhan bisnis ritel menyebabkan persaingan bisnis di pasar penjualan barang dan jasa semakin ketat untuk mencapai keunggulan. Salah satu strategi layanan terbaik untuk memperkenalkan berbagai inovasi perencanaan sumber daya perusahaan adalah dengan menarik konsumen untuk menggunakan layanan tersebut. Penelitian ini bertujuan untuk menguji dan menganalisis hubungan antara praktik manajemen rantai pasok berbasis sistem Enterprise Resource Planning (ERP) dengan kinerja bisnis melalui keunggulan kompetitif bisnis ritel di wilayah Bekasi. Penelitian ini dilakukan dengan menggunakan kuesioner untuk setiap variabel yang disebarkan sebagai pertanyaan yang mewakili dimensi dengan jumlah sampel sebanyak 200 responden. Untuk analisis data digunakan SEM dengan menggunakan software AMOS. Pada akhirnya diperoleh hasil pencarian sebagai berikut: (1) Praktik SCM berpengaruh positif dan signifikan terhadap keunggulan bersaing, hipotesis 1 diterima; (2) Sistem ERP berpengaruh positif dan signifikan terhadap keunggulan bersaing, hipotesis 2 diterima; (3) Praktik SCM berpengaruh positif dan signifikan terhadap kinerja perusahaan, hipotesis 3 diterima; (4) Sistem ERP berpengaruh positif dan signifikan terhadap kinerja bisnis, hipotesis 4 diterima; (5) Keunggulan kompetitif berpengaruh positif dan signifikan terhadap kinerja perusahaan, hipotesis 5 diterima.